Electronic commerce : online consumers' expectations-it's implications for retailers. - Chua, Rinson Hon Liat. (2008)
This study attempts to examine the expectations of consumers with regards to e-retailing. The reasons why consumers use or do not use e-commerce, and the various aspects of a e-commerce transactions are studied.